The Religious Transformation of Kampung ‘Preman’: The History of Islamic Education in Kampung Pancuran Salatiga, 1988-2020 - Sutrisna, Sutrisna (Islah: Journal of Islamic Literature and History, 2024)
This article aims to narrate a chronological history of the religious transformation and the history of Islamic educational institutions in Kampung ‘Preman’ Pancuran Salatiga, with discussions on the history and characteristics of Salatiga society, the stigma and image of Kampung Pancuran, and the history of Islamic educational institutions in Kampung Pancuran. This research is descriptive analytical using historical research methods with a sociological approach to examine the interactions among humans' actions and relations as well as their conditions and consequences. The method consists of heuristics, source criticism, interpretation and historiography. The data used were primary sources, secondary sources, and related literature. The data was collected through interviews, literature study, and desk research. The research results chronology: Salatiga is a city in Central Java Province, located between Semarang and Surakarta, with a diverse population of ethnicities, religions, and cultural traditions. In Dutch colonial period, it was a Christian missionary city called Salatiga Zending, emphasizing education. However, the missionaries were rejected by Muslims and social organisations, and Islam began to develop in Salatiga through education and Islamic boarding schools. Since the colonial period until 1992, Salatiga was administratively structured as one sub-district, Salatiga sub-district, and eight villages or hamlets. One of these villages is Kutowinangun, consisting of seven hamlets or villages. One of these villages is called Pancuran, which is a unique village, ‘different from the others’, with exclusive citizens, and conflicting ‘dual personalities. On the one hand, they have a very strong sense of togetherness, artistic spirit, harmony, unity, solidarity, compassion, and brotherhood. On the other hand, they tend to fight with ‘gangsters’, cause trouble, commit crimes, and play gambling. Therefore, it led to a bad image for its residents. then a negative stigma emerged, that Pancuran as a Kampung ‘Preman’, which is embedded until now. But there is a distinctive aspect of Pancuran village that remains unexposed to the public, i.e. the existence of an Islamic Education Institution in the centre of the village. The history of the establishment of the Pancuran Islamic Education Institute, began in 1988. As the head of the Takmir of Al-Muttaqin mosque in Pancuran, KH Zahroni received waqf from Mrs Muslimah, in a land and house of 199 m2, located on Jl. Talang Tirto 606, Pancuran village. The waqf pledge from Mrs Muslimah (Alwaqif), was intended to serve as a place of Islamic education. The institution was then realized and firmly established on 18 June 1988.